Online and Offline English Learning Systems: Perceptual from Teachers and Students - Irma Irma; Rafiqa Rafiqa; Muhammad Danial (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
Current education issues are online and offline learning systems as a mitigation of learning loss. This study intends to investigate (1) the perception of the teachers and students on online and offline English learning systems and (2) The difficulties of teachers in online and offline English teaching-learning. The study attempted qualitative research. The subject of this study were two English teachers and students of SMPN 3 Tinambung. The data was gathered through questionnaires and interviews. The result indicates (1) The teachers’ and students’ perceptions towards online and offline English learning systems are determined by flexibility, interaction, and knowledge gained. In online learning, teachers have a negative perception of flexibility and interaction and a negative and positive perception of knowledge gained. Students have negative and positive perceptions of flexibility, a negative perception of interaction, and a positive perception of knowledge gained. Teachers and students have positively perceived flexibility, interaction, and knowledge gained on offline learning. (2) The teachers’ difficulties were they had no good internet access and students’ assessments in online teaching. The teachers’ difficulties in the offline class were the students less concentration and focus and classroom management. This paper implies that both online and offline systems have obstacles in the English teaching-learning process